TIC’S: financing, accounting and electronic billing in Mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
The present study is focused on identifying the support and financing programs of the governmental sector that are known and / or used by the MIPyMES in México, in addition, the implementation of the obligatoriness by the fiscal authorities in the sending of the electronic accounting and the process of change from the traditional method to digital in the issuance of tax receipts by Internet. In Mexico, for today’s organizations, information technologies participate in a decisive way in decision-making, which is why it is already compulsory from this year onwards the digitized financial information by the tax authorities as another instrument or indispensable tool to determine tax debats, as well as the obligation for tax payers in the issuance of digital tax receipts over the Internet, considering the limitations and administrative deficiencies, human resources, materials and technology. The objective is to identify the policies implemented by the federal government in Mexico as a strategy in the digital plat form of government financing, accounting and electronic billing programs, the processes of change in the MIPyMES, the main problems for their adaptation to the change in use of icts and propose alternative solutions to the problem. The scope of the present investigation is descriptive. In conclusion, in Mexico, programs have been developed for financing, however, to date no long-term public policy has been formulated that favors MSMEs. The use of icts by the fiscal authority in Mexico are instruments of control and collection in recent years, in addition have allowed a greater fiscal presence.
Keywords: ppublic policies for msmes; use of icts; electronic accounting; electronic invoicing; inspection